2019
DOI: 10.3892/ol.2019.9900
|View full text |Cite
|
Sign up to set email alerts
|

Identification of B‑cell translocation gene 1‑controlled gene networks in diffuse large B‑cell lymphoma: A study based on bioinformatics analysis

Abstract: B-cell translocation gene 1 (BTG1) is a member of the BTG/transducer of Erb family. The present study evaluated the impact of BTG1 gene expression on the clinical outcome of diffuse large B-cell lymphoma (DLBCL) and investigated potential mechanisms using the Gene Expression Omnibus (GEO) database. The gene expression profile datasets GSE31312, GSE10846, GSE65420 and GSE87371 were downloaded from the GEO database. BTG1 expression and clinicopathological data were obtained from the GSE31312 dataset. In 498 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…In the current study we provide the first characterization of BM FL B cell GEP and confirmed their quiescent phenotype, associated with the upregulation of the antiproliferative gene BTG1. Interestingly, a BTG1 hi phenotype was recently associated with a good prognosis in aggressive DLBCL 52 , in association with a decreased cell cycle, confirming a role for BTG1 in the regulation of cell proliferation in GC-derived B-cell lymphomas. The analysis of the interactome between BM FL B cells and EVs-primed BM-MSC highlights not only CXCL12 but also Eph/ephrin pathway.…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…In the current study we provide the first characterization of BM FL B cell GEP and confirmed their quiescent phenotype, associated with the upregulation of the antiproliferative gene BTG1. Interestingly, a BTG1 hi phenotype was recently associated with a good prognosis in aggressive DLBCL 52 , in association with a decreased cell cycle, confirming a role for BTG1 in the regulation of cell proliferation in GC-derived B-cell lymphomas. The analysis of the interactome between BM FL B cells and EVs-primed BM-MSC highlights not only CXCL12 but also Eph/ephrin pathway.…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…The four hub genes we discovered have been studied in multiple tumors. RPL19, which is a tumor-specific antigen of lung adenocarcinoma ( Kuroda et al, 2010 ), can also be used as a prognostic biomarker for prostate cancer ( Bee et al, 2006 ), colorectal cancer ( Huang et al, 2008 ), and diffuse large B-cell lymphoma ( Yan et al, 2019 ). One study ( Bee et al, 2006 ) proposed that the expression of RPL19 in malignant prostate cancer cells was significantly higher than that in prostate cells.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of EEF1D has been identified in glioblastoma, glioma, prostate cancer, colorectal cancer (11), renal papillary cell carcinoma (12), liver cancer (13), oral squamous cell carcinoma ( 14), esophageal cancer (15), and medulloblastoma (16). Furthermore, it has also been found to be significantly overexpressed in 10 different lymphoma isoforms (17). One study confirmed that a high EEF1D mRNA level is associated with lymph node metastasis, advanced stage, and shorter disease-specific survival in patients with esophageal cancer (15).…”
Section: Expression Of Eef1d In Various Tumorsmentioning
confidence: 99%
“…Similar results have also been demonstrated in gastrointestinal cancer (18). However, it is worth noting that the mRNA level of EEF1D in pancreatic cancer shows the opposite trend (17), and the specificreasons for this need to be further explored (Table 1).…”
Section: Expression Of Eef1d In Various Tumorsmentioning
confidence: 99%